2019
DOI: 10.1186/s12903-019-0924-0
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CACS15 regulates tongue squamous cell carcinoma cell behaviors and predicts survival

Abstract: BackgroundThe involvement of lncRNA CASC15 in several types of cancers has been reported, while its role in tongue squamous cell carcinoma (TSCC) is unknown. Our study aimed to investigate the clinical potentials of lncRNA CASC15 in TSCC.MethodsThe expression of CASC15 and miR-124 in tissue samples from TSCC patients and TSCC cell lines was analyzed by qPCR. Overexpression experiments were performed to analyze the interactions between CASC15 and miR-124. Survival analysis was performed to analyze the prognosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…In vivo experiments of the present study demonstrated that CASC15 suppression hampered ESCC xenograft tumor growth. Consistently, previous studies have demonstrated that CASC15 exerted potential oncogenic effects in multiple types of cancer, including tongue squamous cell carcinoma, nasopharyngeal carcinoma, oral squamous cell carcinoma, bladder cancer, melanoma and cervical cancer ( 9 12 , 33 , 34 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In vivo experiments of the present study demonstrated that CASC15 suppression hampered ESCC xenograft tumor growth. Consistently, previous studies have demonstrated that CASC15 exerted potential oncogenic effects in multiple types of cancer, including tongue squamous cell carcinoma, nasopharyngeal carcinoma, oral squamous cell carcinoma, bladder cancer, melanoma and cervical cancer ( 9 12 , 33 , 34 ).…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, lncRNA LOC100133669 facilitates ESCC cell proliferation by regulating Tim50 ( 8 ). CASC15 is an oncogenic factor that has been identified in several types of cancer, such as tongue squamous cell carcinoma, oral squamous cell carcinoma, melanoma and cervical cancer ( 9 12 ). Furthermore, CASC15 expression is upregulated in ESCC ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…36 Wu et al demonstrated that lncRNA CACS15 accelerated the migration and invasion of TSCC cells by down-regulating miR-124. 37 PART1 could mediate the secretion of cytokines and metastasis of tumor cells to affect cancer progression. 15 The expression of PART1 was impeded in glioma tissues and exerted suppressive functions on malignant behavior by targeting miR-190a-3p in glioma cell lines.- 35 Similarly, PART1 was down-regulated in TSCC tissues of patients and a higher level of PART1 was positively correlated with better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed the dysregulation of lncRNAs in TSCC. [35][36][37] Abnormally expressed lncRNAs may exert tumor-promoting or tumor-inhibiting effects and could participate in the regulation of tumor properties in TSCC. 38,39 Thus, lncRNAs may be novel auxiliary diagnostic and therapeutic targets in TSCC.…”
Section: Discussionmentioning
confidence: 99%